Isolation, Screening and Identification of Plant Growth-Promoting Endophytic Bacteria from Theobroma cacao - Simarmata, Rumella; Widowati, Tiwit; Dewi, Tirta Kumala; Lekatompessy, Sylvia J. R.; Antonius, Sarjiya (Biosaintifika: Journal of Biology & Biology Education, 2020)
Cacao (Theobrama cacao) is one of the main plantation commodities in Indonesia which has an important role for the national economy. The low productivity of cacao plants in Indonesia is due to the condition of old plants, pests and diseases attacks which affect the quality of the fruit and decrease the plantâ€™s productivity. The objective of this study was to isolate and identify of endophytic bacteria from stem, flower, leaf and fruit of T. cacao by using 16S rRNA gene as genetic marker. Twenty seven endophytic bacterial isolates were collected from local plantation in Yogyakarta area.Â  From this study, 8 endophytic bacterial strains exhibited the higher PGP traits. The isolates produced Indole Acetic Acid level by 0.3 to 5.21 ppm/hour. All of isolates had nitrogen fixation activity but have not phosphate solubilization activity. Among them, isolates CSDT 4 and CGKBH 4 showed promising potential as PGP bacteria. Based on the 16S rRNA gene sequences, those bacterial strains were identified as Brevibacillus brevis (CSDT 4) and Pantoea sp. (CGKBH 4). We propose that the B. brevis and Pantoea sp. which is reported for the first time for their PGP potential in cacao, exerts its beneficial effects on cacao crop through combined of activities. The potential PGP bacteria from the Cacao plant was used to make a specific bio-fertilizer formula for the Cacao plant, because of the different needs and condition that every plant requires.